Peran Guru dan Pentingnya Menerapkan Karakter Jujur dan Disiplin di Sekolah - Ulfadhilah, Khairunnisa (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2023)
The research carried out provides an overview so that it can identify and instill honest and disciplined character education in students in elementary schools. Character education is an important aspect in forming children's personalities which will influence their behavior and attitudes in the future. The research method used was qualitative with a case study approach at one of the Sangkanurip State Elementary Schools. Data was obtained through observation, in-depth interviews with class teachers, as well as documentation related to learning activities. The research results show that class teachers use various strategies to instill the values ​​of honesty and discipline, including through daily habits, providing real examples, using moral stories, as well as positive and negative reinforcement. Daily habits are carried out through routine activities such as filling out an honesty journal and obeying class rules. Teachers also provide real examples through their own attitudes and behavior that consistently show responsibility, giving examples to students at school such as discipline so that children see it and will gradually follow the example.